2001
DOI: 10.1111/j.1572-0241.2001.03684.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Small Intestinal Nutrient Infusion on Appetite, Gastrointestinal Hormone Release, and Gastric Myoelectrical Activity in Young and Older Men

Abstract: Our findings indicate that aging is associated with nutrient-specific changes in appetite, hormonal, and gastric myoelectrical (EGG) responses to i.d. nutrients. An enhanced satiating effect of small intestinal carbohydrates may potentially contribute to the anorexia of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 29 publications
2
59
0
4
Order By: Relevance
“…Postprandial increases in EGG power have been reported (Smout et al, 1980;Stern et al, 1989;Chen et al, 1991;Kaneko et al, 1995;Kobayashi et al, 1998;Riezzo et al, 2000;Chou et al, 2001) previously andMacintosh et al (2001) reportedthe increase in the EGG power ratio during and after intraduodenal glucose infusion in healthy young and old men.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Postprandial increases in EGG power have been reported (Smout et al, 1980;Stern et al, 1989;Chen et al, 1991;Kaneko et al, 1995;Kobayashi et al, 1998;Riezzo et al, 2000;Chou et al, 2001) previously andMacintosh et al (2001) reportedthe increase in the EGG power ratio during and after intraduodenal glucose infusion in healthy young and old men.…”
Section: Discussionmentioning
confidence: 81%
“…The changes in EGG dominant frequency after glucose intake are similar to the responses to food intake. Whereas some studies (Verhamgen et al, 1998;Macintosh et al, 2001) have shown that the EGG frequency remained unchanged after intraduodenal glucose infusion in healthy young subjects. The mechanism responsible for the increase in EGG dominant frequency during the postprandial period is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…First, only one dose of each peptide was studied; the doses were chosen from our previous studies and aimed to match physiological plasma concentrations of both CCK and GLP-1. Second, only male subjects were investigated as pre- vious findings suggest that young male volunteers have the highest capacity to regulate energy intake in response to energy manipulation (21,22). As a consequence, our observations are valid for young male subjects but cannot necessarily be extrapolated to female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 is secreted from intestinal L-cells in response to the absorption of glucose, other sugars, fatty acids and to a minor extent amino acids (MacIntosh et al 2001;Feinle et al 2002;Brubaker & Anini 2003). The GLP-1 secretory actions of metabolizable nutrients may be linked to cellular ATP generation, K ATP channel blockade and elevation of intracellular Ca 2ĂŸ (Gribble & Reimann 2002).…”
Section: Introductionmentioning
confidence: 99%